Predictors of Patient Satisfaction With Quality of Healthcare in University Hospitals in Ghana - Albert Ahenkan; Kofi Aduo-Adjei (Baqiyatallah University of Medical Sciences, 2017)
Background: For over 2 decades, Ghana's Ministry of Health (MOH) has been resolved to continuously improve the quality of healthcare in a cost-effective manner. Strategies have been adopted to enhance client satisfaction with healthcare services and delivery. Objective: The current study examined patient satisfaction with the quality of healthcare in Ghana by comparing healthcare services at the University of Ghana Hospital (UGH) and the University of Cape Coast Hospital (UCH). Methods: This cross-sectional study was conducted in 2014-2015 with primary data collected from patients at UGH and UCH. Structured questionnaires were administered based on the stratified and convenience sampling methods to select patients receiving healthcare at the outpatients departments of the 2 hospitals. Descriptive statistics and linear regression analysis were used to analyze the data with the help of SPSS version 20. Results: The findings indicated that empathy (β=0.14, P=0.003), communication (β=0.26, P=0.00), culture (β=0.17, P=0.008), tangibles (β=0.12, P=0.040), and priority (β=0.18, P=0.002) are significant predictors of patient satisfaction. Conclusion: Management at the 2 studied hospitals should streamline their quality healthcare policies based on the dimensions of effective communication, empathy, culture, tangibles, and priority to enhance patient satisfaction.